2021
DOI: 10.3390/foods10020367
|View full text |Cite
|
Sign up to set email alerts
|

Language of Administration as a Border: Wild Food Plants Used by Setos and Russians in Pechorsky District of Pskov Oblast, NW Russia

Abstract: Socio-economic changes impact local ethnobotanical knowledge as much as the ecological ones. During an ethnobotanical field study in 2018–2019, we interviewed 25 Setos and 38 Russians in the Pechorsky District of Pskov Oblast to document changes in wild plant use within the last 70 years according to the current and remembered practices. Of the 71 botanical taxa reported, the most popular were Vaccinium vitis-idaea, Vaccinium oxycoccos, Vaccinium myrtillus, Betula spp., and Rumex acetosa. The obtained data was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…Rosaceae led the ranking by a significant margin, followed by Asteraceae and Ericaceae. These results are consistent with the results of field research: Rosaceae and Asteraceae were found to be frequently used by respondents in Europe [ 3 ], including many southern regions once occupied by the USSR [ 6 , 59 ], while Ericaceae, followed by Rosaceae, were predominant in northern regions [ 60 , 61 , 62 ]. The dominance of Rosacea could be seen as an invitation to explore more borderland species.…”
Section: Discussionsupporting
confidence: 90%
“…Rosaceae led the ranking by a significant margin, followed by Asteraceae and Ericaceae. These results are consistent with the results of field research: Rosaceae and Asteraceae were found to be frequently used by respondents in Europe [ 3 ], including many southern regions once occupied by the USSR [ 6 , 59 ], while Ericaceae, followed by Rosaceae, were predominant in northern regions [ 60 , 61 , 62 ]. The dominance of Rosacea could be seen as an invitation to explore more borderland species.…”
Section: Discussionsupporting
confidence: 90%
“…However, our observations and the respondents' reports confirmed that movements along this border still exist nowadays. This unique similarity across state borders stands in contrast with the findings of Stryamets et al [15], who highlighted the similarity between two ethnic groups (the case of the Hutsuls and Romanians) within the same country (Romania or Ukraine), while they found higher differences within groups across the border (Romanians living in Romania and Ukraine) and Belichenko et al [35] for Seto people residing on the border between Estonia and Russia.…”
Section: Transitional Knowledge Over State Borders: Differences and S...contrasting
confidence: 71%
“…The currently obtained cross-border difference (JI = 54) is comparable with the high similarity (JI = 53) between Muslim and Kakai Kurds in Iraq [16]; while the dissimilarity between Hawraman and Mukriyan Kurds in Western Iran (JI = 35) resembles the difference between Muslim Kurds and Assyrians (J = 32) and Assyrians and Yazidis (JI = 34) in Iraq [32]. The cross-border JIs in DiGe studies [10] varied from 65 among Setos in Estonia and Russia, where the border was merely administrative until 30 years ago [35], to 55 among Hutsulsin Romania and Ukraine, where the solid border was established over 75 years before the study [8]. At the same time, the Polish-Belarus-Lithuanian borderlands ranged from 48 to 62, as in that once homogenous region, the borders shifted several times in the last 75 years [20].…”
Section: Transitional Knowledge Over State Borders: Differences and S...mentioning
confidence: 99%
“…Several researchers have noted changes in the use of natural resources [ 21 ] (p. 60) and significant divergence in LEK between the divided border communities [ 22 , 23 ], despite many years of living together in the same area and sharing the same religious faith [ 24 ], as well as accessing multilingual folk and scientific literature regarding the use of wild plants [ 25 ]. In this vein, various ethnobotanical border studies have found that differences within the compared ethnic groups are more pronounced than those with other local communities currently inhabiting the same country [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%